Single-step surgery for treating chronic periodontitis and increasing the width of keratinized gingiva in Mandibular Anterior Region: A case report - Madhuri Alankar Sawai; Ashu Bhardwaj; Zeba Jafri; Nishat Sultan; Anika Daing (Wolters Kluwer Medknow Publications, 2021)
Chronic periodontitis is precipitated as periodontal pockets, gingival recession (GR), decreased keratinized gingiva, and vestibular depth (VD). In the mandibular anterior region, it is frequently seen as GR and decreased VD. The development of high frenal attachment due to loss of periodontal support further increases the rate of progression of the disease and compromises the condition of the incisors. As mandibular incisors have short roots, they usually tend to become mobile early during the progression of periodontal disease. In this case report, a single-step surgery was done, which included periodontal flap surgery with bone augmentation in relation to mandibular anterior teeth. Following this, the width of keratinized tissue was increased using Diode laser by deepening the vestibule. This combined procedure can cover the exposed roots and increase the width of keratinized gingiva.